1995
DOI: 10.1136/bmj.310.6975.293
|View full text |Cite
|
Sign up to set email alerts
|

Drug injection and HIV prevalence in inmates of Glenochil prison

Abstract: Objective-To determine prevalence of HIV infection and drug injecting behaviour among inmates of Glenochil Prison on a specified date a year after an outbreak of hepatitis B and HIV infection.Design-Cross sectional: voluntary, anonymous HIV salivary antibody surveillance and linked self completion questionnaire on risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
73
0
1

Year Published

1996
1996
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(81 citation statements)
references
References 6 publications
7
73
0
1
Order By: Relevance
“…It cannot be ruled out that the availability of sterile equipment may have facilitated initiation of injecting drug use in these persons. However, it is more likely that this finding reflects the natural incidence of injection drug use among inhalational heroin users in settings where peers frequently inject [1,5]. Overall, there was no evidence that the availability of sterile syringes led to an increase in drug consumption.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…It cannot be ruled out that the availability of sterile equipment may have facilitated initiation of injecting drug use in these persons. However, it is more likely that this finding reflects the natural incidence of injection drug use among inhalational heroin users in settings where peers frequently inject [1,5]. Overall, there was no evidence that the availability of sterile syringes led to an increase in drug consumption.…”
Section: Discussionmentioning
confidence: 92%
“…Injection drug use in prison carries a substantial risk of infection with bloodborne viruses such as human immunodeficiency virus (HIV), hepatitis B virus (HBV) and hepatitis C virus (HCV) [1][2][3][4][5][6][7]. Prevention strategies are needed to reduce the risk of infection among incarcerated injecting drug users (IDUs).…”
Section: Introductionmentioning
confidence: 99%
“…14,16 A number of studies conducted in the United States and elsewhere have found that a substantial proportion of prisoners engage in highrisk sexual activity and/or intravenous drug use while in prison. 14,16,17 In a recent Scottish study 5 it was demonstrated that 27% of the inmates reported injecting drug usage any time in life. Of those, 59% admitted using it inside the prison, of which a quarter had their first experience with injecting drugs in prison.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Many studies have shown that the prevalence of HIV infection is higher in the incarcerated population than in the general population, [4][5][6][7] and more recently other studies have shown that a greater proportion of inmates are infected with HCV than with HIV. [8][9][10][11][12][13][14] People admitted to correctional facilities often have a history of injection drug use, needle-sharing and high-risk sexual behaviours.…”
mentioning
confidence: 99%